Emerging role of METTL3 in inflammatory diseases: mechanisms and therapeutic applications - Song, Bimei; Zeng, Yue; Cao, Yanqing; Zhang, Jiamin; Xu, Chao; Pan, Yaping; Zhao, Xida; Liu, Jingbo (Frontiers in Immunology, 2023)
Despite improvements in modern medical therapies, inflammatory diseases, such as atherosclerosis, diabetes, non-alcoholic fatty liver, chronic kidney diseases, and autoimmune diseases have high incidence rates, still threaten human health, and represent a huge financial burden. N6-methyladenosine (m6A) modification of RNA contributes to the pathogenesis of various diseases. As the most widely discussed m6A methyltransferase, the pathogenic role of METTL3 in inflammatory diseases has become a research hotpot, but there has been no comprehensive review of the topic. Here, we summarize the expression changes, modified target genes, and pathogenesis related to METTL3 in cardiovascular, metabolic, degenerative, immune, and infectious diseases, as well as tumors. In addition to epithelial cells, endothelial cells, and fibroblasts, METTL3 also regulates the function of inflammation-related immune cells, including macrophages, neutrophils, dendritic cells, Th17 cells, and NK cells. Regarding therapeutic applications, METTL3 serves as a target for the treatment of inflammatory diseases with natural plant drug components, such as emodin, cinnamaldehyde, total flavonoids of Abelmoschus manihot, and resveratrol. This review focuses on recent advances in the initiation, development, and therapeutic application of METTL3 in inflammatory diseases. Knowledge of the specific regulatory mechanisms involving METTL3 can help to deepen understanding of inflammatory diseases and lay the foundation for the development of precise targeted drugs to address inflammatory processes.